Inventarisasi, Pendampingan Dan Penulisan Sejarah Keluarga Veteran Di Kota Jambi - Itawan, Devi; Saumia, Zulfa; Lestari, Inda; Saputra Adiguna, Richad; Hudaya, Padhil (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Veterans of the war of independence revolution are key witnesses in the history of the Indonesian people's struggle to seize and maintain independence and post-independence. The stories of the sacrifices of these heroic veterans are the most common examples of Indonesian nationalism. However, after Indonesia's independence lasted for 78 years. The stories of the sacrifices of these heroic veterans are the most common examples of Indonesian nationalism. The increasingly old age of the veterans makes it necessary to carry out documentation of historical sources owned by these veterans in a memoir and write their experiences in a book. The Community Service Team of the History Study Program, University of Jambi, held an inventory, mentoring and writing of the history of veteran families in Jambi City. It is hoped that this activity can provide an example and raise nationalism among the young generation of Jambi today.